The Effect of Live Streaming Quality on Purchase Intention through Immersive Experience, Consumer Trust, and Perceived Value (Study of This is April Consumers on TikTok) - Oktaviani, Rosana; Murwani, F. Danardana; Hermawan, Agus (International Journal of Business, Law, and Education, 2024)
Live-streaming shopping has become a new trend since the pandemic in 2020 where live streamers promote and sell products to consumers via social media channels by increasing intimacy and communication. This Is April is one of the leading fashion brands in Indonesia that focuses on fulfilling women's desires for fashionable, affordable and high-quality clothes, shoes, and bags. This Is April also continues to carry out promotions by keeping up with developments in consumer behavior that continues to change, one of which is by carrying out promotions by selling via live streaming on one of the e-commerce sites (TikTok). This study aims to investigate the effect of live streaming quality (LSQ) on purchase intention (PI) through immersive experience (IE), consumer trust (CT), and perceived value (PV) at This is April consumers on TikTok by answering 10 (ten) hypotheses. This research uses a quantitative approach using partial least squares equation model (PLS-SEM). The samples in this study were respondents who had experience in watching live streaming of This is April fashion products on TikTok within the last 3 (three) months and respondents who lived in the city of Malang using a non-probability sampling technique. The analysis results show that LSQ has a positive and significant effect on PI. Furthermore, the research results show that IE, CT, and PV are able to mediate the relationship between LSQ and PI. The implication of this finding can provide a theoretical basis and reference for seller of fashion clothing products to focus their attention on the important of effectively leverage live streaming quality to develop immersive experience, consumer trust, and perceived value to influence purchase intention